Who Remembers Better? Sex Differences in Memory Among Higher Education Students in Nepal - Koirala, Bhasha (Social Inquiry: Journal of Social Science Research, 2021)
There are manifestations that conclude sex plays a role in the memory function and thus sex tends to favour a memory type. This comparative study was conducted with higher education boy and girl students to assess the difference in different types of memory between sexes. The assessment done was based on Post Graduate Institute (PGI) memory scale developed by Pershad and Wig (1988). Sex was sole independent variable and dependent variables were ten memory subscales. Data collected were analysed by computing the mean and t-test. Comparison between two groups indicates significant difference in five subscales i.e., remote memory, recent memory, mental balance, attention and concentration and retention of dissimilar pairs. Among five subscales except in recent memory male score has outperformed and the difference in the score was significant. As such computing mean also demonstrated higher mean average in male side. However, the difference in memory between male and female has been demonstrated to some extent though it has followed distinct pattern.